Parametric Study of the Rectangular Microstrip Antenna using Cavity Model - Jamal W. Salman; Mudhaffer M. Ameen; Star O. Hassan (Journal of Engineering and Sustainable Development, 2006)
A cavity model well suited for computer aided design is presented and developed to study the rectangular microstrip antenna. The patch is described by geometrical and electrical parameters. The resonant frequency, resonant resistance, bandwidth, efficiency and other electrical parameters of RMSA have been presented as a function of varying the patch dimension and substrate parameters. The accuracy and usefulness of the method are investigated through comparison with experimental results as well as other previous theoretical methods.